Impacto de intervenções no controle da infecção do trato urinário associada ao cateterismo vesical de demora - Silva, Myria Ribeiro da [UNIFESP] (2016)
Quasi-experimental epidemiological study design type before and after, in order to analyze the impact of educational interventions for prevention and control of urinary tract infection in patients bladder catheterization procedure takes. The population consisted of 124 nursing professionals, 36 nurses and 88 nursing technicians. Data collection was carried out through an instrument that addressed the characterization of population data and knowledge related to care in the insertion, during installation, to maintenance and considerations on withdrawal. This research consisted of three periods: a period of preintervention, a period of intervention and other post-intervention. The predominance of the participants were female (82.3%), double employment (54.8%), age of 36 years professional experience on average of 9.2 for both categories, and experience in institution with a total average of 5.5 years for the two functions. It was built a scale of 20 items composed of five subscales. To analyze the knowledge and behavior of CVD procedure, we used the descriptive statistical analysis, distribution in relative and absolute frequencies, mean, standard deviation, Levene test for equality of variances (p value, z value, assumed), t test for independent samples (t value, degrees of freedom, p value), non-parametric inferential tests and chi-square test (?2). To analyze the change in the pattern of pre-test behavior to post-test through the global scale, we used analysis of covariance, in which set the regression line between the pre and post-test, by professional category. Significance level p<0.05. In the overall shape analysis, the relationship of the scores on the scale in the pre-test and post-test, it is observed that in the case of category E, the adjusted equation Y=0,015X+19,61, It indicates that regardless of the starting point in the pre-test, almost all professionals came to answer all 20 questions correctly. Similarly, the nursing technicians category fitted equation Y=0,003X+18,70, also did not matter the level in the pretest, the educational intervention brings to 19 the expected level of correct answers. There was an evolution in the knowledge level after the educational interventions for the group formed by E and TE. Therefore, it is concluded that the actions were effective and should be implemented by the nursing staff periodically, considering that these may influence the quality of care and professional.